R for SAS and SPSS users - Muenchen, Robert A. (Statistics and computing, 2011)
R is a powerful and free software system for data analysis and graphics, with over 4,000 add-on packages available. This book introduces R using SAS and SPSS terms with which you are already familiar. It demonstrates which of the add-on packages are most like SAS and SPSS and compares them to R's built-in functions. It steps through over 50 programs written in all three packages, comparing and contrasting the packages' differing approaches. The glossary defines R terms using SAS/SPSS terminology and again using R terminology. The table of contents and the index allow you to find equivalent R functions by looking up both SAS statements and SPSS commands. The second edition adds 216 pages of new topics. I found the book extremely helpful. The material is laid out in a way that makes it very accessible. Because of this I recommend this book to any R user regardless of his or her familiarity with SAS or SPSS. For new R users it will demystify many aspects, and for existing R users it will have many answers to those questions you have been too afraid to ask in public.